AUDIT OF APPROPRIATENESS AND OUTCOME OF COMPUTED TOMOGRAPHY BRAIN SCANNING FOR HEADACHES IN PAEDIATRIC AGE GROUP - Nawaz, Muhammad; Amin, Ayesha; Qureshi, Ahmad Nadeem; Jehanzeb, Muhammad (Journal of Ayub Medical College Abbottabad, 2009)
Background: Headache is a common complaint in children. With the proliferation of brain imaging centers and the increasing patient demand for CT or MRI studies, brain imaging has become widely used to evaluate headache and exclude malignant lesion. The objectives of this descriptive study were to assess the appropriateness and outcomes of computed tomography brain scanning for headaches in paediatric age group. This study was conducted at the Radiology Department Hayatabad Medical Complex, Peshawar over a period of 1 year July 2008-July 2009. Methods: Both genders between the ages of 4-18 years included in the study presenting with headache either isolated or common/classic migraine were included in this study. These variants of headache were allocated an appropriateness rating of 2 for CT scan by the American College of Radiology Appropriateness Criteria (ACRAC) for children with headaches. Results: Out of the 100 patients only 4% patients showed abnormal findings on CT scan while the remaining 96% of the scans were absolutely normal. The four patients with abnormal findings all had sinusitis no notorious lesions. Conclusion: This audit suggests that a proportion of the computed tomography studies performed for children with isolated headaches or common/classic migraine may have been inappropriate. The development of a local guideline for imaging referral is indicated. Keywords: Children, Headache, Computed tomography